Inverse analysis for transmissivity and the Red river bed’s leakage factor for Pleistocene aquifer in Sen Chieu, Hanoi by pumping test under the river water level fluctuation - Huy, Trieu Duc; Thanh, Tong Ngoc; Lam, Nguyen Van; Hoang, Nguyen Van (Vietnam Journal of Earth Sciences, 2018)
Aquifer parameters and riverbed hydraulic resistance to an aquifer have an important role in the quantitative assessment of groundwater sources, especially the aquifer recharge from river. The analytical determination of aquifer parameters and riverbed hydraulic resistance to the aquifer is rather complicated in case if the water level in the river fluctuates before and during the pumping test time. This is especially true for Pleistocene aquifer along the Red River in Hanoi city, where the riverbed has been changed very much during the recent decades. A trial-error inverse analysis in the parameters’ determination by a group pumping test data obtained with a test located close to the Red river bank in Sen Chieu area, Phuc Tho district, Hanoi city was carried out. Before and during the pumping test time the water level in the river changed five times. The results have shown that the Pleistocene aquifer has a relatively high hydraulic conductivity of 55.5 m/day, which provides a good role in the transport of a large volume of water recharged by the river to the abstraction wells located near the river. The aquifer storage coefficient had lightly decreased with the pumping time, which is corresponding to the physical nature of that the aquifer stativity is a function of the aquifer pressure. A special point is worthwhile to be noted that the Red river bed resistance to the Pleistocene is very low, about 0.537 days, which is corresponding to the increase of the distance from the river bank further from the well in 28.4 m to have the river as a specified water level boundary of the aquifer. In contrast, the 1990’s investigations had found that the Red river bed resistance to the Pleistocene aquifer to be about 130 days (Tran Minh, 1984), which is corresponding to the increase of the distance from the river bank further from the well in a thousand of meters to have the river as a specified water level boundary for the aquifer. References Christensen S., 2000. On the estimation of stream flow depletion parameters by drawdown analysis. Ground Water, 38(5), 726-734. Fetter C.W., 2001. Applied Hydrogeology. Prentice Hall-Upper Saddle River, NJ 07458. Fletcher G. Driscoll., 1987. Groundwater and Wells. Published by Johnson Division, St. Paul, Minnesota 55112, USA. Fox G.A., 2004. Evaluation of a stream aquifer analysis test using analytical solutions and field data. Journal of the American Water Resources Association. 40(3), 455-763. Hunt B., Wei J. and Clausen B., 2001. A stream depletion field experiment. Ground Water 39(2), 283-289. John H. Cushman and Daniel M. Tartakovsky (Editors), 2017. The Handbook of Groundwater Engineering. Third Edition. CRC Press. Taylors & Francis Group. 6000 Broken Sound Parkway NW, Suite 300. Lough H.K. and Hunt B., 2006. Pumping test evaluation of stream depletion parameters. Ground Water. Jul-Aug, 44(4), 540-546. Mironhenco V.A. and Shestakov V.M., 1974. Fundamentals of hydromechanics. Publishers "Nedra", Moscow, Russia. Ne-Zheng Sun, 1994. Inverse Problems in Groundwater Modeling. Cluwer Academic Publishers. Nguyen Minh Lan, 2014. Report on "Study of the relationship between the Red river and groundwater, proposal of methods of determination of groundwater abstraction potential along the Red river from Son Tay to Hung Yen". Code: TNMT.02.33. Nguyen Quoc Thanh and Nguyen Van Hoang, 2007. Hydrogeomechanical processes affecting the stability of Red river dike’s foundation and in the Son Tay-Ha Noi area. Hanoi Geoengineering 2007. International Conference Proceedings, 120-123. Nguyen The Chuyen, Vu Ngoc Duc, Dao Trong Tu, Nguyen Van Hoang, 2017. Study on determination of effective porosity and longitudinal dispersivity of aquifer and the application to field tracer injection test in Mo Lao, Ha Dong area, Hanoi, Vietnam. Vietnam National University Journal of Science, 33(1), 1-15. Nguyen Van Giang, Nguyen Ba Duan, Le Ngoc Thanh, Noboru Hida, 2014. Hydro-geophysical Techniques to Aquifer Locating and Monitoring for Industrial zone north Thang Long and Quang Minh, Hanoi. Vietnam J. Earth Sci., 36(3), 221-232. Doi: 10.15625/0866-7187/36/3/5905. Nguyen Van Hoang, 2016. Modelling of water pollution. Vietnam Academy of Science and Technology Publishers. Pham Dinh, 2016. Report on "Study of the effects of the sand and gravel excavation in the Red river and Thai Binh river system on the flow regime and bed load regime for supporting sustainable management and planning of sand and gravel excavation" code ĐTĐL.2012-T/27. Vietnam Academy of Water Resources. Sophocleous M., 2001. Interactions between groundwater and surface water: the state of the science. Hydrogeology Journal, 10, 52-67. Tong Ngoc Thanh, Trieu Duc Huy, Nguyen Van Kenh, Tong Thanh Tung, Pham Ba Quyen, Nguyen Van Hoang, 2017. Methodology of determining effective porosity and longitudinal dispersivity of aquifer and the application to field tracer injection test in Southern Hanoi, Vietnam. Vietnam J. Earth Sci., 39(1), 57-75. Doi: 10.15625/0866-7187/39/1/9228. Tran Minh, 1984. Report on "Results of groundwater investigation in Hanoi area". Northern Union for Water Resources Planning and Investigation. Trieu Duc Huy (Project head), 2015. Proposal "Groundwater protection in large cities (Hanoi city)" and the project’s implementation data and materials. Vietnam National Center for Water Resources Planning and Investigation. Vu Tat Uyen and Le Manh Hung, 2011. Warning on the consequences of sand and gravel excavation in the Red river more than the annual bed load supply. Journal of Water Resources Science and Technology, 3, 2-6.